PLURALISME, TOLERANSI, PENDIDIKAN MULTIKULTURAL DAN KERUKUNAN UMAT BERAGAMA - Jamalie, Zulfa (LP2M IAIN Palangka Raya, 2012)
In public life a very plural, distinction because both tribes, language, culture, customs, all the more sothe difference understand and religion, is very prone to the incidence of conflict and contradiction. In the field of religious life, the attitude of intolerance and mutually hostile, could well arise due to frictions due to differences of religious doctrine, the doctrine of deployment or implementation of services by their respective religions. For its numerous attempts have been made by the Government in order to achieve harmony between religious life, whether through education, out reach, and mentoring and various other ways, because harmony is an absolute requirement for the Government to carry out the construction. Of course the efforts and programs that have been launched by the Government will not work optimally if not supported by all components of the society and all the people of religion. Therefore the development of an attitude of tolerance, pluralism, mutual respect and appreciate between believers and between groups who have the difference understand is very important to do. How exactly the strategy or efforts should be done to make it happen?